حفظُ الكرامة في نقد أخبارٍ منسوبة إلى الصحابيّ محلِّم بنِ جثَّامة رضي الله عنه - ربوزي, سمير (جامعة الوادي - University of Eloued, 2022)
عرفَت بعض دواوين السنة، وكثير من كتب التفسير، والتاريخ، والسير، والتراجم، وغيرها تساهلا في نقل بعض الأخبار الواهية والمكذوبة؛ فحصل بذلك شرّ عظيم، بلغ في أحيان كثيرة حدّ المساس بأقدار بعض أنبياء الله تعالى، وأصحاب النبي صلى الله عليه وسلم. من هذه الأخبار ما روي في تفسير آيةٍ من سورة النساء، نزلت عتابا لصحابيٍّ قتل رجلا أظهر إسلامه، نقل بعض أهل العلم الإجماع على أن هذا الصحابي هو محلّم بن جثامة رضي الله عنه، على الرغم من أن الآية جاءت تخاطبه ومَن معه، وليس هذا وحسب؛ بل ورد في مصنفات عديدة أن محلّما دعا عليه النبي صلى الله عليه وسلم فمات بعد سبعة أيام، فلما دفنه قومه لفظته الأرض ثلاث مرات! فألقوا عليه الحجارة وأكلته السباع! نحاول في هذه الدراسة أن نقف على أدلة الموردين لهذه الأخبار، ومدى تثبّتهم من صحتها. Some collections of the Sunna and many books of exegesis, history, biographies and others, by being lenient in transmitting fake and distorted information, caused great evil that reached sometimes, even trespassing against the rank of some Prophets of Allah and Companions of the Prophet -peace and blessings be upon him-. Such information includes what is narrated when interpreting a verse in sura An-Nisâ', which is revealed as a blame towards one who kills a man after pronouncing the testimony of faith. Some scholars have reported that there is agreement among scholars that it concerns Muhallim Ibn Jaththâma -may Allah be pleased with him-, though the verse in question is intended for him and those who were with him alike. Moreover, it is reported in many collections that the Prophet -peace and blessings be upon him- invoked Allah against Muhallim and he died after seven days and when his people buried him, the earth rejected his body three times, sot they threw stones on him and beasts ate him! We will try in this study to analyze the proofs of each group who brought this information and the extent of checking its authenticity.
مقال
Keywords: الصحابة؛ محلّم بن جثامة؛ القتل العمد؛ لفظته الأرض؛ التثبت; Companions; Muhallim Ibn Jaththâma, deliberate killing; earth rejected his body; checking authenticity